2014
DOI: 10.6002/ect.2013.0122
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: There are numerous changes in inflammatory status that occur after a kidney transplant. Pentraxin 3 is a marker of inflammation, but little information is available about pentraxin 3 levels after a kidney transplant. We evaluated the relation between pentraxin 3 and other inflammatory markers including high sensitivity C-reactive protein, interleukin 6, and tumor necrosis factor α in kidney transplant recipients. Materials and Methods: Adult patients (40 patients; aged, 18-80 y; mean age, 38 ± 10 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…According to our study, changes in PTX-3 after transplantation were significant. Contrary to our findings, Gursu et al suggested that PTX-3 may not help diagnose inflammatory conditions after kidney transplantation and CRP may be better than PTX-3 as a marker of inflammation (28). In their study, after transplantation, the mean CRP and IL-6 levels decreased but the PTX-3 and TNF-α levels did not change and a significant correlation was found between IL-6 and CRP before and after transplantation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…According to our study, changes in PTX-3 after transplantation were significant. Contrary to our findings, Gursu et al suggested that PTX-3 may not help diagnose inflammatory conditions after kidney transplantation and CRP may be better than PTX-3 as a marker of inflammation (28). In their study, after transplantation, the mean CRP and IL-6 levels decreased but the PTX-3 and TNF-α levels did not change and a significant correlation was found between IL-6 and CRP before and after transplantation.…”
Section: Discussioncontrasting
confidence: 99%
“…They found no significant association between TNF-α and hs-CRP hypersensitivity before transplantation, but a significant correlation was reported after transplantation. There was no significant association between IL-6 and PTX-3, TNF-α and PTX-3, or hs-CRP and PTX-3 before or after transplantation (28). The findings of the study by Gursu and colleagues were contrary to us and the reason for this difference is unclear.…”
Section: Discussionmentioning
confidence: 56%
“…Increased IL-6 leads to chronic inflammatory conditions such as the synthesis of acute phase proteins like CRP, hypercoagulability and accelerated atherosclerosis. [7], [28], [29], [30], [31] that can cause to the loss of renal function [7]. Also, some mechanisms including volume overload and oxidative stress can cause the usual increase in inflammatory symptoms (including IL-6) [32].…”
Section: Discussionmentioning
confidence: 99%